(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
This research paper examines how social dynamics shape environmental decision-making by analyzing qualitative data on public perceptions of climate change. Understanding these perceptions is crucial as they influence individual and collective actions toward climate adaptation and mitigation. The study synthesizes findings from various cultural contexts, highlighting the roles of gender relations, social capital, and cultural knowledge in shaping responses to climate change. The analysis reveals that social norms, trust, and community networks significantly impact environmental decisions. The paper underscores the importance of integrating social dynamics into climate policies to foster effective and inclusive environmental action.